Carbon nanoparticle coated by silicon dioxide supported platinum nanoparticles towards oxygen reduction reaction. (July 2021) - Qin, Yanxi; Yang, Xiaobo; Li, Rongyu; Chen, Shuai; Wang, Yunwei; Yu, Zhimin; Wang, Yingyong; Liu, Xingchen; Tong, Xili
Graphical abstract: Highlights: SiO2 thin-layer coated carbon black (SiO2 -C) was synthesis successfully. SiO2 -C exhibits the excellent anti−CO and methanol poisoning ability for ORR reaction. The mechanism of ORR process for Pt/SiO2 -C were verified by DFT calculations. Abstract: Herein, a SiO2 thin-layer is coated on the surface of carbon nanoparticles. Such a composite is further utilized as the support to load Pt nanoparticles (Pt/SiO2 -C). This Pt/SiO2 -C catalyst features an improved interaction between Pt nanoparticles and the stable SiO2 thin-layer. In acid media, an optimal Pt/SiO2 -C catalyst displays significantly improved ORR activity (e.g., a half-wave potential of 0.81 V vs. RHE and a limiting diffusion current of 5.55 mA cm −2 ) and enhanced ability towards CO andmethanol anti-poisoning. Such performance is superior to the commercial Pt/C catalysts, Pt/carbon nanoparticle based catalysts, and Pt catalysts deposited on other supports. As predicted by density functional theory calculations (DFT), such high ORR performance is mainly due to the reduced free energy barrier, derived from the hydrophilic of SiO2 thin-layer.